EFEKTIVITAS STRATEGI PEMBELAJARAN BRAIN-BASED LEARNING TERHADAP KETERAMPILAN METAKOGNITIF - Aidil Adhani; Silfia Ilma (Universitas Lambung Mangkurat, 2017)
Abstract. Thinking skills is strongly influenced by the working of brain. The brain is the center of all activities including thinking. Therefore, the learning that regard and develop brain potential to develop high order thinking skills in students is required. The reason to do this research is because the lack of training given to students in optimizing the ability of their brain in thinking, which generally use the lower order thinking such as remembering and memorizing. The use of Brain-Based Learning (BBL) strategy will be an opportunity for students to develop their thinking skills for their cognitive achievement. This research aims to determine the effectiveness of BBL strategy to metacognitive skills of biology students in Borneo Tarakan University. This is quasi experiment research with pretest-posttest control group design. Population in this research is all of biology students who program Cell Biology course. Students of A and B class are the sample of this research. Data analysis used is descriptive and inferential statistic technique. The results showed that BBL strategy is more effective influencing metacognitive skills compared with multistrategy. The average score in the class with BBL is 51.81 higher than the average score on the class taught with multistrategy that is 41.94.Keywords: Brain-Based learning, thinking skills, metacognitive.